Positive Welfare and the Like: Distinct Views and a Proposed Framework - Rault, Jean-Loup; Hintze, Sara; Camerlink, Irene; Yee, Jason Richard (Frontiers in Veterinary Science, 2020)
Positive welfare and related terms such as good welfare, happiness and a good life are increasingly used in the animal welfare science literature. Overall, they highlight the welfare benefits of providing animals opportunities for positive experiences, beyond the alleviation of suffering. However, the various terms remain loosely defined and are sometimes used interchangeably, resulting in discrepancy. In this perspective article, we lay out the terms and concepts used in the literature. We identify two distinct views: ‘hedonic positive welfare’, arising from likes and wants and their positive outcomes on welfare; and ‘positive welfare balance’, as an overall positive welfare state based on positive experiences outweighing negative ones. Eudaimonia, satisfaction with one’s life, may emerge as a third view. We propose a framework that is applicable across the views. The ‘Vienna framework’ outlines different facets: frequency, duration, intensity, context, previous experience, individual differences, sense of agency, and long-term benefit. The framework aims to encourage researchers to consider the relevance of these facets for their research, to indicate how the facets are affected by different interventions (e.g. greater sense of agency in enriched compared to non-enriched animals), or to compare different topics with respect to the different facets (e.g. high intensity of play behaviour and low intensity of social affiliation). We encourage researchers to carefully consider and clearly state how their work falls along these views and facets, conceptually and operationally. This should prevent dilution of the meaning of positive welfare and thereby preserve its potential to improve the welfare of animals.